Estudios eidéticos Una conversación desde el Sur sobre la vida de las ideas y la reconfiguración de un espacio disciplinar - Devés, Eduardo (Ariadna Ediciones, 2018)
Its purpose is to publish works that point, in particular, to the studies of thought, in its varied expressions and its connections with realities not properly eidetic: networks, institutionality, intellectual environments, circulation of ideas, among others. It appears after years of redefinition in the South American environment, where people have been articulated that constitute the diverse groups that cultivate this disciplinary field, and where specialists with greater trajectory converge with others who are initiated in these tasks, although already committed in this direction with research and publications. The public to which the Collection is directed is integrated, both by specialists in this field and by people interested in the life of ideas. Some of the issues that most interest the Collection, consist of updating the studies of intellectual history and ideas that have been produced in the South American region and in various disciplinary areas: the eidetic circulation between Chile - and South America - the wide world, theoretical and methodological issues that contribute to the development of this disciplinary field, highlighting those who have cultivated this field, reissuing classic works.